Strategi Digital untuk UMKM: Pelatihan Dasar Pemanfaatan Marketplace di Pusat Kegiatan Belajar Masyarakat (PKBM) Teuku Markam Aceh Utara - Husniati, Ade Muana; Maryam; Mardhiah, Ainol; Johan, Muhammad; Muzaffarsyah, Teuku (Universitas Malikussaleh, 2025)
Basic digital marketing and marketplace utilization training is a strategic step in improving community skills in the digital era, especially for groups that have not yet been fully exposed to technology. Community Learning Activity Centers (PKBM) play a crucial role in providing access to non-formal learning that empowers communities economically and socially. This article discusses basic digital marketing and marketplace utilization training for participants in the sewing skills program at PKBM Teuku Markam, covering its objectives, materials, methods, benefits, impacts, and implementation recommendations. This training is designed to equip participants, mostly women with basic education backgrounds, with practical skills in utilizing digital media for marketing and managing online stores. The impact of this training included increased participants' understanding of digital marketing concepts, technical skills in creating marketing content, and the courage to launch online businesses, a concept previously unimaginable for most participants. Several participants successfully created their own online store accounts, uploaded their products to marketplaces, and used social media for promotion. This demonstrates that digital training can be a catalyst for community-based economic transformation, particularly in areas with limited access to formal training. Furthermore, this training fostered collaboration between educational institutions, industry practitioners, and local communities as a holistic approach to community economic empowerment. Continuous evaluation and cross-sector collaboration are highly recommended to ensure the sustainability of this program and anticipate future developments in digital technology.